Students’ Verbal Impoliteness Outside of the Classroom - Ali Wira Rahman; Rizka Indahyanti (Universitas Cokroaminoto Palopo, 2015)
This research concerning on the students’ verbal impoliteness outside of the classroom, when they were associate with others friends. This research aimed to found the type of impoliteness they use d and how far it influences the relationship each other. This research was conducted using qualitative research, more specific including as discourse analysis. The population were the English students of Universitas Muhammadiyah Parepare and the subject were two students of the sixth semester. The data were collected by observation, interview, Recording and the data analysis using discourse analysis method namely by extracting all of the conversation to be analyzed. The result of this research showed that (1) the three types of impoliteness used in the verbal communication of the students outside of the classroom. (2) the closer the relationship, the more impolite the verbal communication will be.